2021
DOI: 10.1021/acs.orglett.1c02536
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Switched Manganese(I)-Catalyzed Regiodivergent Distal vs Proximal C–H Alkylation of Imidazopyridine with Maleimide

Abstract: A sustainable Mn­(I)-catalyzed exclusive solvent-dependent functionalization of imidazopyridine with maleimide via an electrophilic metalation at the distal (in 2,2,2-trifluoroethanol (TFE)) and chelation assisted at the proximal (in tetrahydrofuran (THF)) has been developed. The strategy was successfully applied to the drug Zolimidine and a broad range of substrates, thereby reflecting the method’s versatility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 63 publications
0
42
0
Order By: Relevance
“…A KIE ( k H / k D ) value of 1.7 was detected, thereby indicating that the C–H cleavage step might be involved in the rate-determining step. Based on preliminary mechanistic studies and literature precedent, 5 a plausible reaction mechanism is outlined. A cationic Rh(III) catalyst undergoes the C–H activation process with 1a to produce a rhodacycle intermediate A .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A KIE ( k H / k D ) value of 1.7 was detected, thereby indicating that the C–H cleavage step might be involved in the rate-determining step. Based on preliminary mechanistic studies and literature precedent, 5 a plausible reaction mechanism is outlined. A cationic Rh(III) catalyst undergoes the C–H activation process with 1a to produce a rhodacycle intermediate A .…”
Section: Results and Discussionmentioning
confidence: 99%
“… 4 To address these issues, maleimides have been intensively employed as succinimide precursors in the transition-metal-catalyzed C(sp 2 )–H and C(sp 3 )–H alkylation reactions ( Scheme 1 ). 5 Mechanistically, succinimide adducts are generated via a 1,4-addition pathway, where the migratory insertion of internal olefins of maleimides is followed by the protonation of the C–metal intermediates. Alternatively, maleimides can undergo migratory insertion, syn -coplanarity arrangement, and β-hydride elimination or E1cB elimination to afford olefinated compounds, 6 which can be further trapped by internal nucleophiles through a Michael-type reaction to produce spirosuccinimides.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in 2021, the Patel group demonstrated the Mn( i )-catalyzed regiodivergent C–H alkylation of imidazopyridine and imidazopyridine-fused scaffolds 69a with N -substituted maleimides 69b (Scheme 69). 141 The regioselectivity was controlled by the solvent system. In the presence of tetrahydrofuran (THF) solvent, the catalytic system afforded ortho -C–H alkylation of arenes to form 69c through chelation assisted metalation.…”
Section: Alkylation Via C–h Bond Activationmentioning
confidence: 99%
“…29 To give a few examples regarding chelation-assisted functionalizations: Patel's research group demonstrated a solvent-controlled regiodivergent Mn-catalyzed alkylation of imidazo[1,2- a ]pyridine with maleimide. 32 Wang et al successfully executed a domino arylation reaction of 2-arylimidazo[1,2- a ]pyridines under Pd-catalysis. 33 Metal-catalyzed alkenylation and annulation reactions of 2-arylimidazo[1,2- a ]pyridines have also been reported recently.…”
Section: Introductionmentioning
confidence: 99%